Pendidikan Politik : Solusi Meningkatkan Partisipasi Pemilih Pemula Dalam Pemilihan Umum di Negeri Kedah Malaysia (Kolaborasi Pengabdian Internasional) - Prihatin, Panca Setyo; Ibrahim, Ahmad Zubir; Abdillah, Satrio; Adni, Dita Fisdian (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to increase young voters’ knowledge, awareness, and participation in Kampung Singkir Darat, Negeri Kedah, Malaysia, about their rights and obligations in general elections through political education. The method of implementing this service uses counselling, which includes planning, implementation, and monitoring with partners Universiti Utara Malaysia. The instrument for evaluating this activity is a questionnaire, which is then analyzed descriptively. This service showed that young voters’ knowledge, awareness, and participation in Kampung Singkir Darat, Negeri Kedah, Malaysia, increased their rights and obligations in general elections. This activity can increase community participation among those aged 18-21 years so that smart and quality elections can be carried out.